A Potent and Selective Dual Inhibitor of AXL and MERTK Possesses Both Immunomodulatory and Tumor-Targeted Activity - Rios-Doria, Jonathan; Favata, Margaret; Lasky, Kerri; Feldman, Patricia; Lo, Yvonne; Yang, Gengjie; Stevens, Christina; Wen, Xiaoming; Sehra, Sarita; Katiyar, Kamna; Liu, Ke; Wynn, Richard; et al. (Frontiers in Oncology, 2020)
TYRO3, AXL, and MERTK constitute the TAM family of receptor tyrosine kinases, which play important roles in tumor growth, survival, cell adhesion, as well as innate immunity, phagocytosis, and immune-suppressive activity. Therefore, targeting both AXL and MERTK kinases may directly impact tumor growth and relieve immunosuppression. We describe here the discovery of INCB081776, a potent and selective dual inhibitor of AXL and MERTK that is currently in phase 1 clinical trials. In cellular assays, INCB081776 effectively blocked autophosphorylation of AXL or MERTK with low nanomolar half maximal inhibitory concentration values in tumor cells and BAF3 cells transfected with constitutively active AXL or MERTK. INCB081776 inhibited activation of MERTK in primary human macrophages and partially reversed M2 macrophage–mediated suppression of T-cell proliferation, which was associated with increased interferon-γ production. In vivo, the antitumor activity of INCB081776 was enhanced in combination with checkpoint blockade in syngeneic models, and resulted in increased proliferation of intratumoral CD4+ and CD8+ T cells. Finally, antitumor activity of INCB081776 was observed in a subset of sarcoma patient–derived xenograft models, which was linked with inhibition of phospho-AKT. These data support the potential therapeutic utility of INCB081776 as an immunotherapeutic agent capable of both enhancing tumor immune surveillance and blocking tumor cell survival mechanisms.